2015
DOI: 10.1071/hc15198
|View full text |Cite
|
Sign up to set email alerts
|

Optimising neurosurgical outpatient care: a paradigm shift?

Abstract: INTRODUCTION: The Wellington Regional Hospital (WRH) neurosurgical service has noted a substantial increase in patient volumes over the last decade, with referrals to the neurosurgical outpatient clinic appearing to have increased even more substantially. AIM: To quantify the increase in referrals to the WRH neurosurgical outpatient service and to determine whether this has translated into an increase in the number of neurosurgical procedures performed. METHODS: All referrals to the WRH neurosurgical departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Probably, before GPs referred patients for neurosurgical consults, they should consider other therapies, such as physical medicine evaluation, infiltrative corticosteroid therapy or evaluation by another specialist. The fact that this does not happen may be due to the lack of guidelines to help general practitioners refer patients with spinal diseases to the neurosurgeon, as also confirmed by a study by Kamat et al [ 3 ] These authors also showed neurosurgeons spend most of their time screening patients rather than operating on them and that an increased number of outpatient clinics did not result in an increased number of surgeries [ 3 ]. Therefore, the development of relevant guidelines for the referral of primary care to a neurosurgery service appears justified and could facilitate the initiation of appropriate investigations in primary care.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Probably, before GPs referred patients for neurosurgical consults, they should consider other therapies, such as physical medicine evaluation, infiltrative corticosteroid therapy or evaluation by another specialist. The fact that this does not happen may be due to the lack of guidelines to help general practitioners refer patients with spinal diseases to the neurosurgeon, as also confirmed by a study by Kamat et al [ 3 ] These authors also showed neurosurgeons spend most of their time screening patients rather than operating on them and that an increased number of outpatient clinics did not result in an increased number of surgeries [ 3 ]. Therefore, the development of relevant guidelines for the referral of primary care to a neurosurgery service appears justified and could facilitate the initiation of appropriate investigations in primary care.…”
Section: Discussionmentioning
confidence: 96%
“…In other countries similar studies have been performed. For example Kamat et al [ 3 ] showed that specialist referrals result in a proportionally greater number of therapeutic surgical interventions than GP referrals. They concluded that the development of relevant guidelines for primary care referral to a neurosurgical service, could facilitate initiation of appropriate investigations in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…As the population ages and lives longer with chronic disease, DSC are regularly called upon to deliver complex care to complex patients. In medicine, there are many examples of a shift from inpatient procedures to outpatient care, which suggests that the differences between teaching hospitals and DSC are reducing.…”
Section: Patient Outcomesmentioning
confidence: 99%